Quantifying the ultrastructure changes of air-dried and irradiated human amniotic membrane using atomic force microscopy: a preliminary study - Mohd, Suhaili; Ghazali, Mohamad Izhar; Yusof, Norimah; Sulaiman, Sofiah; Ramalingam, Saravana; Kamarul, Tunku; Mansor, Azura (Springer, 2018)
Air-dried and sterilized amnion has been widely used as a dressing to treat burn and partial thickness wounds. Sterilisation at the standard dose of 25 kGy was reported to cause changes in the morphological structure as observed under the scanning electron microscope. This study aimed to quantify the changes in the ultrastructure of the air-dried amnion after gamma-irradiated at several doses by using atomic force microscope. Human placentae were retrieved from mothers who had undergone cesarean elective surgery. Amnion separated from chorion was processed and air-dried for 16 h. It was cut into 10 × 10 mm, individually packed and exposed to gamma irradiation at 5, 15, 25 and 35 kGy. Changes in the ultrastructural images of the amnion were quantified in term of diameter of the epithelial cells, size of the intercellular gap and membrane surface roughness. The longest diameter of the amnion cells reduced significantly after radiation (p < 0.01) however the effect was not dose dependent. No significant changes in the shortest diameter after radiation, except at 35 kGy which decreased significantly when compared to 5 kGy (p < 0.01). The size of the irradiated air-dried amnion cells reduced in the same direction without affecting the gross ultrastructure. At 15 kGy the intercellular gap decreased significantly (p < 0.01) with Ra and Rq, values reflecting surface roughness, were significantly the highest (p < 0.01). Changes in the ultrastructure quantified by using atomic force microscope could complement results from other microscopic techniques.